Statistical characteristics of cost contingency in water infrastructure projects - Baccarini, David; Love, Peter (American Society of Civil Engineers, 2014)
Cost contingency is one component of a project’s budget to cater for cost growth. The determination of a project’s cost contingency is a pervasive problem because the amount that is incorporated into an estimate is invariably insufficient to accommodate the cost growth of a project. This study analyzed the statistical characteristics of cost contingency and cost growth experienced in 228 similar Australian water infrastructure projects that were procured by using traditional lump contracts. It was revealed that mean project final costs exceeded the approved budgets that contained contingency. The mean contingency percentage addition was 8.46%, yet the mean contingency required for the final cost was 13.58% for the sampled projects. Thus, the deterministic percentage addition, used by the sponsor to accommodate for cost growth beyond their baseline budget, was inaccurate. To improve the accuracy of a contingency estimate, the empirical distributions of cost contingency and cost performance were examined to determine their best-fit probability distribution. The research presented in this paper demonstrates that determining the best fit probability distribution provides a more robust and defendable basis for selecting a cost contingency than the traditional deterministic percentage approach.